Life cycle greenhouse gas emissions of diesel oil and zero-emission trucks: Systematic review of status and perspectives - Gaia Gentilucci; Antonella Accardo; Ezio Spessa (Transportation Research Interdisciplinary Perspectives)
The transport sector is a major source of greenhouse emissions, requiring urgent action for transition to cleaner alternatives. In this context, Zero Emission Vehicles (ZEVs) are essential for decarbonizing the transport sector and reducing air pollution. To estimate the potential benefits and burdens of these novel powertrains, the Life Cycle Assessment (LCA) methodology can be used and offer a comprehensive approach. However, when comparing ZEVs to diesel Internal Combustion Engine Vehicles (ICEVs), it is crucial to rely on robust results to ensure comparability. The present study presents a systematic literature review of LCA applications to Heavy-Duty Vehicles (HDVs), employing a rigorous methodology to provide an unbiased and comprehensive overview. The study aims to: (1) investigate the state-of-the-art methodological approaches in LCA implementation to HDVs (i.e., qualitative assessment) and (2) quantify the carbon footprints of current ICE-HDVs and ZEVs (i.e., quantitative assessment). After a screening step, a sample of 24 publications, comprising both scientific articles and industrial reports, has been extracted from several databases. Quantitatively, the analysis highlights a significant variability of the carbon footprint results, ranging between 431–1780 tons CO2eq for diesel ICEVs, 175–1626 tons CO2eq for battery electric vehicles, 366–2944 tons CO2eq for fuel cell electric vehicles. Instead, from the qualitative standpoint, the review reveals that, while quite consensus exists on the functional unit, there are still major differing methodological choices that cause significant variability of carbon footprint among studies. Also, the analysis highlights the strong need for improved primary data coverage and greater harmonization of LCA methods and assumptions.